Children’s right to remedy, as part of their protection - Lux, Ágnes (European Integration Studies, 2023)
A complaint mechanism is a procedure and tool by which children who believe that their rights have been violated seek a remedy and end to the violation. The right to remedy is a core human right, and the basic dimension of children’s access to justice and the recognition that children are full citizens are crucial to being protected. In most cases, independent children/human rights institutions (ICRIs) function as ombudsman offices, which are (mostly) complaint driven. If an institution has broad competence, it should determine within its structure either an identifiable commissioner or special unit/division responsible for children’s rights. A complaint can also be seen as an essential and direct source of information about children’s lives and problems, as well as a tool for ICRIs to propose amendments to policies and legislation. However, research has clearly shown that children and young people comprise a very small proportion of ICRI complaints. Why is that so? There is a lack of information and trust in public institutions. This may be due to the belief that complaints are not taken seriously, and perhaps due to fear of negative or retaliatory consequences. Therefore, complaint mechanisms are not sufficiently accessible to children and should be made more child-friendly. There is an important new international forum of complaints that can be analyzed here: the UN Committee on the Rights of the Child. Here, individuals or groups can make complaints regarding the violation of children’s rights since the Third Optional Protocol of the UN Convention on the Rights of the Child entered into force.